2017
DOI: 10.1155/2017/4898057
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Concentrated Bone Marrow Grafting for the Treatment of Osteonecrosis of the Humeral Head: A Report of Five Shoulders in Four Cases

Abstract: Five shoulders in four patients affected by advanced osteonecrosis of the humeral head were treated with autologous concentrated bone marrow grafting. Bone marrow sample was aspirated from the iliac crests, concentrated by a centrifugation technique, and injected into the necrotic site. The shoulders were evaluated radiologically with X-ray scoring and clinically with measurement of range of motion and pain score (visual analogue scale, VAS). The mean follow-up period was 49.4 (range, 24–73) months. The concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Six year post-operative outcomes of proceeding concentrated autologous bone marrow aspirate transplantation (CABMAT) resulted in the successful prevention of femoral head collapse [169]. Clinical evaluation of the spared joints in autologous concentrated bone marrow grafting conducted on four patients affected by advanced osteonecrosis resulted in recovery and improved motion [170]. The yearlong human model study by De Riu et al demonstrated efficacy of bone marrow nucleated concentrate (BMNc) in patients with degenerative temporomandibular joint disorders (TMDs).…”
Section: Bone Marrow Mononuclear Cells and Bone Marrow Concentratementioning
confidence: 99%
“…Six year post-operative outcomes of proceeding concentrated autologous bone marrow aspirate transplantation (CABMAT) resulted in the successful prevention of femoral head collapse [169]. Clinical evaluation of the spared joints in autologous concentrated bone marrow grafting conducted on four patients affected by advanced osteonecrosis resulted in recovery and improved motion [170]. The yearlong human model study by De Riu et al demonstrated efficacy of bone marrow nucleated concentrate (BMNc) in patients with degenerative temporomandibular joint disorders (TMDs).…”
Section: Bone Marrow Mononuclear Cells and Bone Marrow Concentratementioning
confidence: 99%
“…30 Bone grafting, either simple autologous grafting, strut bone graft or vascularised bone graft are complex procedures with increased morbidity and variable results. 31,32 It remains unclear as to the most effective joint sparing treatment of osteonecrosis. The natural history of conservatively treated advanced osteonecrosis of the humeral head is poor.…”
Section: Discussionmentioning
confidence: 99%
“…Previous systemic reviews into the management of gleno-humeral ON are limited [5]. A variety of different surgical techniques have been described to deliver improved clinical outcomes for patients with symptomatic ON by a number of authors [1,3,8,9,14,19,21]. These include core decompression, autologous concentrated bone marrow grafting, hemiarthroplasty, total shoulder arthroplasty and reverse shoulder arthroplasty.…”
Section: Discussionmentioning
confidence: 99%